A phase 2 study of alpha interferon for molecularly measurable residual disease in chronic myeloid leukemia after allogeneic hematopoietic cell transplantation. Issue 11 (19th September 2019) - Bezerra, Evandro D.; Flowers, Mary E.; Onstad, Lynn E.; Chielens, Deborah; Radich, Jerald; Higano, Celestia S.
Abstract: CML therapy has improved dramatically with the development of tyrosine kinase inhibitors (TKIs). Prior to the TKI era, we conducted two trials of alpha-interferon (IFN) for post-transplant hematologic and cytogenetic relapse. The complete cytogenetic response rate was 33% and 57% respectively. This report describes a third trial in which 40 patients with molecular relapse between 6 and 12 months post-transplant were treated with IFN. The projected cytogenetic relapse at 4.5 years was 12.6% compared with 42% in the historical control group. Although this data may not apply to most patients with CML today due to the availability of multiple TKIs, the effectiveness of short term IFN in post-transplant molecular relapse is supported by long-term treatment-free-survival in 75% of patients after a median follow-up of 15.6 years. This report suggests that alpha-interferon is potentially useful in the rare patient who has post-transplant molecular relapse who does not tolerate, or is resistant to TKIs.